Identification and Comparative Genomic Analysis of Type VI Secretion Systems and Effectors in Klebsiella pneumoniae - Li, Wanzhen; Liu, Xiaofen; Tsui, Waitang; Xu, An; Li, Dan; Zhang, Xuefei; Li, Pei; Bian, Xingchen; Zhang, Jing (Frontiers in Microbiology, 2022)
Klebsiella pneumoniae is a nosocomial opportunistic pathogen that can cause pneumonia, liver abscesses, and infections of the bloodstream. The resistance and pathogenicity of K. pneumoniae pose major challenges to clinical practice. However, the ecology and pathogenic mechanisms of K. pneumoniae have not been fully elucidated. Among these mechanisms, the secretion systems encoded by strains of the bacteria confer adaptive advantages depending on the niche occupied. The type VI secretion system (T6SS) is a multi-protein complex that delivers effector proteins to the extracellular environment or directly to eukaryotic or prokaryotic cells. T6SSs are widely distributed in Gram-negative bacteria and play an important role in bacterial virulence and the interactions between bacteria and other microorganisms or the environment. This study aimed to enhance the understanding of the characteristics of T6SSs in K. pneumoniae through an in-depth comparative genomic analysis of the T6SS in 241 sequenced strains of K. pneumoniae. We identified the T6SS loci, the synteny of the loci in different species, as well as the effectors and core T6SS-related genes in K. pneumoniae. The presence of a T6SS was a common occurrence in K. pneumoniae, and two T6SS clusters are the most prevalent. The variable region downstream of the gene vgrG usually encodes effector proteins. Conserved domain analysis indicated that the identified putative effectors in K. pneumoniae had the functions of lipase, ribonuclease, deoxyribonuclease, and polysaccharide hydrolase. However, some effectors did not contain predicted functional domains, and their specific functions have yet to be elucidated. This in silico study represents a detailed analysis of T6SS-associated genes in K. pneumoniae and provides a foundation for future studies on the mechanism(s) of T6SSs, especially effectors, which may generate new insights into pathogenicity and lead to the identification of proteins with novel antimicrobial properties.